PROJECTS ON AIRPORTS, AIRFIELDS, HELICOPTER AERODROMES AND LANDING GROUNDS SANITARY PROTECTION AREAS AS THE BASIS OF THEIR ACTIVITY COMPLIANCE ASSESSMENT TO ECOLOGICAL REQUIREMENTS - O. A. Kartyshev; N. I. Nikolaykin (Научный вестник МГТУ ГА, 2017)
Ten years experience of the development of domestic airports sanitary protection zones projects in civil aviation based on Sanitary Regulations and Norms 2.2.1/2.1.1.1200-03 requirements is analyzed, the reasons of loss of quality of project works and delaying of coordination terms at the last stage of the development are established. It is shown that among the main reasons for current negative situation with projects development and coordination are: absence of a check algorithm of settlement borders of areas and contours of aviation noise with the use of natural researches methods in Sanitary Regulations and Norms 2.2.1/2.1.1.1200-03; absence of methods of amendment in projects and regulations of establishment of the airport sanitary protection zones final dimensions. Examples of oversized and undersized noise areas and ones of the polluting substances dispersion as well as the reasons of local authorities’ interests in it are given.Conceptional strategies which should be used in the edition of a new Russian conservancy normative document regulating the development of projects on sanitary protection areas. New document will allow to consider various factors of negative environmental impact of the airports, airfields, helicopter aerodromes and landing grounds activities.It is offered to introduce the concept of "aviation noise set index operational card", which will solve the legitimation problem of the aviation noise account in the State Immovable Property Cadaster. Suggestions on equivalent and maximum level magnitude of the sound made at the residential territory of cities and urban-type settlements by flights and aircraft ground operation are given.Standards are supposed to be harmonized with similar international rules and have to provide zone gradation by 5 dBA.Suggestions on the considerations of the revealed deficiencies are made, requirements to project sections structure of sanitary protection zones are formulated, proposals on the establishment of aviation noise hygienic standards on the airports aerodrome environs are offered.